A new species of Domene Fauvel, 1873 (Coleoptera: Staphylinidae: Paederinae) from a granitic cavity in Serra da Estrela (Portugal) - Serrano, Artur R.m.; Conde, José; Antunes, Sandra; Aguiar, Carlos A.s.; Boieiro, Mário (Zootaxa, 2015)
A new species of the genus Domene Fauvel, 1873—D. viriatoi n. sp.—is described from a granitic natural cavity in Serra da Estrela, Portugal. This subterranean species is diagnosed and compared with closely related species from the Iberian endemic subgenus Lathromene Koch, 1938. The external morphology and male genitalia are illustrated and information on the species` ecology is presented. A dichotomic key to the Lathromene species based on the male genitalia is provided. The need to protect the habitat of this species from human disturbance is commented on.